The affair : a Jack Reacher novel - Child, Lee (Child, Lee. Jack Reacher novel, 2015)
Carter Crossing, Mississippi. 1997. A lonely railroad track. A crime scene. A coverup. A young woman is dead, and solid evidence points to a soldier at a nearby military base. But that soldier has powerful friends in Washington. Reacher is ordered undercover--to find out everything he can, to control the local police, and then to vanish.